2017
DOI: 10.1515/revecp-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Shadow Economy in the Czech Regions: A Region-Level Study

Abstract: This paper investigates the size and development of the shadow economy in the Czech Republic on the state-level base over the 2005-2014 period. The multiple indicators multiple causes (MIMIC) model is used to assess the estimation of the shadow economy size. I investigate how labour market, number of people with at least one distraint, and the burden of taxation might contribute to the existence of the shadow economy. While the former two are important determinants of the shadow economy, I find no evidence to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…In this context, the researchers have concentrated on the factors behind cross-country differences in the size of the shadow economy considering its unfavorable social, institutional, and economic implications. The relevant literature has elicited that tax and social security burden, regulations, corruption, institutional and legal quality, GDP per capita, inflation, unemployment, and financial sector development are the major factors contributing to the survival of the shadow economy (Ruge, 2010;Bose et al, 2012;Mara & Sabău-Popa, 2013;Remeikiene et al, 2014;Buček, 2017). However, relatively fewer researchers have explored the influence of economic freedom and globalization, two prominent properties of the global economy during the past four decades.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the researchers have concentrated on the factors behind cross-country differences in the size of the shadow economy considering its unfavorable social, institutional, and economic implications. The relevant literature has elicited that tax and social security burden, regulations, corruption, institutional and legal quality, GDP per capita, inflation, unemployment, and financial sector development are the major factors contributing to the survival of the shadow economy (Ruge, 2010;Bose et al, 2012;Mara & Sabău-Popa, 2013;Remeikiene et al, 2014;Buček, 2017). However, relatively fewer researchers have explored the influence of economic freedom and globalization, two prominent properties of the global economy during the past four decades.…”
Section: Introductionmentioning
confidence: 99%
“…Population / Population density. Densely populated areas tend to have lower levels of the shadow economy (Buček, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Previous findings concerning the main determinants of the shadow economy in regions are reviewed in Table 1. As it can be seen in Table 1, the determinants of the shadow economy may vary from region to region, although some general tendencies can be envisaged: many authors highlight the significance of taxation (Bilonizhko, 2006;Tafenau et al, 2010;Buehn, 2012;Polovyan, 2015;Gonzalez-Fernandez & Gonzalez-Velasco, 2015;Gasiūnas, 2018;Remeikiene et al, 2018;Davydova et al, 2020), standard of living (Kireenko et al, 2017;Remeikiene et al, 2018), labour market (Bilonizhko, 2006;Tafenau et al, 2010;Buehn, 2012;Vorobyev, 2015;Buček, 2017;Prytula et al, 2019), institutional factors (Polovyan, 2015) and corruption (Vorobyev, 2015;Borlea et al, 2017;Gillanders & Parviainen, 2018). Nevertheless, the results of some studies are contradictory, for instance, Buček's (2017) study found no evidence to prove the importance of particular types of taxes (e.g.…”
Section: Regional Shadow Economy and Its Determinants: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of research and statement of the problem. Theoretical considerations and empirical researches into the size and development of the shadow economy are presented in the studies of such authors as F. Schneider [1, 2, 7, 10], A. Buehn [1], M. Hassan [2], J. Buček [3], Yu. Kharazishvili [4][5]; T. Putnins, A. Sauka [6]; R. Goel, J. Saunoris [7]; T. Tiner [8], etc.…”
Section: оцінка рівня I природа тіньової економікиmentioning
confidence: 99%